Tuberculous Splenic Abscesses as an Etiology in Prolonged Fever - Dolvy Girawan; S A Abdurachman; Iman Supandiman; Hadi Jusuf; Tan Siauw Koan; Warko Karnadihardja (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2005)
Extra-pulmonary tuberculosis covers all forms of tuberculosis in which the disease process occurs outside the lungs. Tuberculosis is one of the common infectious causes of splenic enlargement, but tuberculous splenic abscess is a rare presentation. We report the finding of tuberculous multiple splenic abscesses in a young male patient aged 33 years with prolonged fever. The main clinical feature was fever for 6 months prior to admission. Abdominal ultrasound revealed the spleen was normal in size but showed multiple abscesses. CT scan abdomen showed splenomegaly with multiple solid nodules. Patient underwent laparatomy and splenectomy, the spleen indeed showed multiple abscesses. Histopatology Result showed Langhan’s multi nucleated giant cells, caseous necrosis. The patients was diagnosed to have tuberculous multiple abscesses of the spleen. The patient was started  on  daily  short-course  antituberculosis  drugs  with  isoniazid,  rifampicin, pyrazinamide and ethambutol. He responded well to oral antituberculosis treatment.   Keywords: prolonged fever, abdominal ultrasound, CT scan abdomen, tuberculosis, multiple splenic abscesses, splenectomy